Analisis kesesuaian lahan dan daya dukung ekologis untuk wisata rekreasi pantai di kawasan ekowisata pesisir Deaga, Kabupaten Bolaang Mongondow Selatan (Analysis of land suitability and ecological carrying capacity for beach recreation in the coastal ecotourism area of Deaga, southern Bolaang Mongondow Regency) - Rauf, Aprianto; Djamaluddin, Rignolda; Wantasen, Adnan S (Universitas Sam Ratulangi, 2020)
Coastal tourism industry grows very fast, so it is very potential to be used as an alternative business to increase the income and welfare of coastal communities. The development of an optimal tourism area requires good planning and management. This study assesses the suitability of land for coastal recreational tourism activities in Deaga Village, Southern Bolaang Mongondow Regency, by measuring the biophysical and supporting parameters at 8 observation stations on Deaga Beach, as well as the ecological carrying capacity of the environment calculated by considering the ecological potential of visitors. The results of the analysis of the suitability of tourism in Deaga Village are categorized as ‘very suitable’ for beach recreation activities with ecological carrying capacity that can accommodate 113 visitors per day. Thus, the coastal recreation tourism business in Deaga Village is very potential to be developed; and by paying attention to the ecological carrying capacity, this can be sustainable.—Pertumbuhan industri pariwisata pesisir berlangsung sangat cepat sehingga sangat potensial dijadikan alternatif usaha untuk meningkatkan pendapatan dan kesejahteraan masyarakat pesisir. Pengembangan kawasan wisata yang optimal memerlukan perencanaan dan pengelolaan yang baik. Penelitian ini menilai kesesuaian lahan untuk kegiatan wisata rekreasi pantai di Desa Deaga, Kabupaten Bolaang Mongondow Selatan, dengan mengukur parameter biofisik dan penunjang di 8 (delapan) stasiun pengamatan di Pantai Deaga serta daya dukung ekologis lingkungan, yang dihitung dengan mempertimbangkan potensi ekologis pengunjung. Hasil analisis menunjukkan, kesesuaian lahan wisata di Desa Deaga dikategorikan ‘sangat sesuai’ untuk kegiatan rekreasi pantai dengan daya dukung ekologis yang dapat menampung wisatawan 113 orang/hari. Dengan demikian, usaha wisata rekreasi pantai di Desa Deaga sangat potensial dikembang; dan dengan memperhatikan daya dukung ekologis, maka usaha ini dapat berkelanjutan.